Renal replacement therapy after liver transplantation - S. V. Zhuravel; Ye. N. Dorofeyeva; N. K. Kuznetsova; A. O. Chugunov; V. V. Kiselev; A. M. Talyzin; L. V. Donova; A. V. Chzhao (Трансплантология (Москва), 2018)
Objective: to analyze the causes of acute renal failure (ARF) and to study the efficiency of renal replacement therapy (RRT) in the treatment of this condition after liver transplantation.Materials and methods. Eighty liver transplantations made at the N.V. Sklifosovsky Research Institute of Emergency Care from 2000 to 2008 were analyzed. The patients were divided into 2 groups: 1) 29 patients with evolving ARF who received RRT in the postoperative period; 2) 51 patients who had no indications for RRT.Results. Postoperative RRT was performed in 29 (36.3%) patients. Of them, 23 patients had been identified to have the hepatorenal syndrome in the preoperative period. Renal function recovered in 20 (72.4%) of the 29 patients who needed RRT during the performed treatment and they were discharged from the clinic. Due to the conducted treatment, these patients showed stabilization and their ARF resolution occurred within 12.7±6.2 days. The mean number of performed sessions required to restore renal function was 8.8 (range 1 to 56).Conclusion. Preoperative hepatorenal syndrome is a predictor of ARF in the postoperative period. At the same time ARD has a good prognosis after liver transplantation. With a primary non-functioning graft, extracorporeal techniques are ineffective and maintenance therapy used prior to liver retransplantation.